An ideal universal host for highly efficient full-color, white phosphorescent and TADF OLEDs with a simple and unified structure. Issue 39 (3rd October 2017) - Gao, Kuo; Liu, Kunkun; Li, Xiang-Long; Cai, Xinyi; Chen, Dongjun; Xu, Zhida; He, Zuozheng; Li, Binbin; Qiao, Zhenyang; Chen, Dongcheng; Cao, Yong; Su, Shi-Jian
Abstract : Via employing a unique universal host, highly efficient full-color, white phosphorescent and TADF OLEDs were achieved with a simple and unified structure. Abstract : The actualization of highly efficient full-color and white organic light-emitting diodes (OLEDs) in a simple and unified device architecture using host materials that are suitable for red, green, and blue dopants has been quite a challenge. Herein, a series of thioxanthene and 9-phenylcarbazole hybrids were designed and synthesized, among which 9, 9′-((9 H -thioxanthene-9, 9-diyl)bis(3, 1-phenylene))bis(9 H -carbazole) (m-DCz-S) exhibited unique universal host characteristics. Full-color OLEDs were fabricated with phosphorescent and thermally activated delayed fluorescent (TADF) emitters, i.e. FIr6, Ir(ppy)3, PO-01, 2CzPN, ACRDSO2, and PyCN-ACR; among these, the FIr6-based blue device showed the best performance reported to date. In addition, the phosphorescent white OLED with complementary emitters, FIr6: PO-01, has high efficiencies of 61.4 cd A −1, 62.9 lm W −1, and 25.0% and extremely good color stability with a color variation less than (0.0007, 0.0007) in the whole range of luminance. Further improved efficiencies of 74.3 cd A −1, 82.7 lm W −1, and 26.4% have been achieved in the case of the phosphorescent white OLED based on FIrpic: PO-01, which is the most efficient white OLED with this simplified structure reported to date. It is worth noting that all the devices have been fabricated with the same extremely simple architecture by solely changing the emitters doped into the host; thus, the unique universal host material m-DCz-S is advantageous for future low-cost and highly efficient OLED application.